Perylene tetracarboxylate surfactant assisted liquid phase exfoliation of graphite into graphene nanosheets with facile re-dispersibility in aqueous/organic polar solvents. (August 2017) - Narayan, Rekha; Lim, Joonwon; Jeon, Taewoo; Li, Dong Jun; Kim, Sang Ouk
Abstract: Liquid phase exfoliation (LPE) is a promising method for graphene production particularly in terms of cost effectiveness and scale up. Nonetheless, it is still challenging to synchronize prime goals of high quality, good yield, large sheet size, stable long term storage and low cost eco-friendly processing. We present a simple and inexpensive green route for large scale production of exfoliated graphene dispersions exploiting the non-covalent surface chemistry between graphene and perylene tetracarboxylate (PTCA) aromatic semiconducting surfactant. Direct sonication of graphite flakes in aqueous PTCA solutions produced high yield of single and few-layer graphene sheets with minimal basal plane defects as revealed by XPS, Raman and FTIR spectroscopy. Uniquely for LPE protocol, the lateral graphene flake dimensions extended upto 10–12 μm range. The exfoliated dispersions exhibited high colloidal stability with shelf-life exceeding a year. Facile re-dispersibility of the dried graphene/PTCA powders was observed in water as well as many polar organic solvents. Significantly, pure aromatic semiconducting nature of surfactant without dielectric moiety ensures tight electrical contact among graphene sheets in thin films. The approach exploiting the simple molecular design of aromatic charged surfactants for graphene exfoliation holds a great prospect for solution processed graphene based nanomaterials and devices. Graphical abstract: